2015
DOI: 10.1128/iai.02404-14
|View full text |Cite
|
Sign up to set email alerts
|

Protective and Pathological Functions of CD8+T Cells in Leishmania braziliensis Infection

Abstract: dCutaneous leishmaniasis (CL) caused by Leishmania braziliensis is characterized by a strong Th1 response that leads to skin lesion development. In areas where L. braziliensis transmission is endemic, up to 15% of healthy subjects have tested positive for delayed-type hypersensitivity to soluble leishmania antigen (SLA) and are considered to have subclinical (SC) infection. SC subjects produce less gamma interferon (IFN-␥) and tumor necrosis factor alpha (TNF-␣) than do CL patients, but they are able to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 40 publications
5
106
1
2
Order By: Relevance
“…Although excessive IFN-γ and cytotoxic CD8 + T cells may contribute to the inflammatory response that leads to ulcer development [3739], the importance of IFN-γ as a defense mechanism in CL is well established. Suppressed production of IFN-γ is associated with systemic spread of L .…”
Section: Discussionmentioning
confidence: 99%
“…Although excessive IFN-γ and cytotoxic CD8 + T cells may contribute to the inflammatory response that leads to ulcer development [3739], the importance of IFN-γ as a defense mechanism in CL is well established. Suppressed production of IFN-γ is associated with systemic spread of L .…”
Section: Discussionmentioning
confidence: 99%
“…Blood was collected and a biopsy was performed for immunological studies. The patient had a viral load of 89,296 copies/mL, CD4 + cell counts of 105 cells/ mm 3 , and CD8 + cell counts of 422 cells/mm 3 . Antiretroviral therapy with tenofovir, lamivudine, and efavirenz was started.…”
Section: Resultsmentioning
confidence: 99%
“…In November 2013, the patient returned for follow-up, and total scar formation was observed in the lesion. At this time the patient presented with undetected viral load, CD4 and CD8 cell counts of 171 and 409 cells/mm 3 , respectively. Immunological results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, hyperinfl ammatory collateral damage from T helper type 1 (Th1) response has been reported, along with a variable T helper type 2 (Th2) response dependent on cytokine release and other T cells (12) (13) . Moreover, Cardoso et al (14) demonstrated that cluster of differentiation 8 (CD8) + T cells in patients with subclinical Leishmania braziliensis infection secrete interferon gamma (IFN-γ) to activate macrophages and facilitate parasite clearance. Notably, Pereira-Carvalho et al (15) showed that T cells maintain activation levels at approximately 2 years after the end of therapy, and lymphocytes from well-healed lesions recognize leishmanial stimuli and proliferate upon exposure.…”
mentioning
confidence: 99%